Holoprosencephaly: recommendations for diagnosis and management - Kauvar, Emily F. (2010)
PURPOSE OF REVIEW: This review presents recent advances in our understanding and clinical management of holoprosencephaly (HPE). HPE is the most common developmental disorder of the human forebrain and involves incomplete or failed separation of the cerebral hemispheres. The epidemiology, clinical features, causes, diagnostic approach, management, and outcomes of HPE are discussed. RECENT FINDINGS: Chromosomal abnormalities account for the most commonly identified cause of HPE. However, there are often unidentifiable causes in patients with nonsyndromic, nonchromosomal forms of HPE. The prevalence of HPE may be underestimated given that patients with mild forms often are not diagnosed until they present with severely affected children. Pregestational maternal diabetes mellitus is the most recognized risk factor for HPE, as supported by recent large-scale epidemiological studies. Genetic studies using microarray-based comparative genomic hybridization technology have resulted in better characterization of important HPE loci. SUMMARY: HPE encompasses a wide spectrum of forebrain and midline defects, with an accompanying wide spectrum of clinical manifestations. A coordinated, multidisciplinary care team is required for clinical management of this complex disorder. Further research will enable us to better understand the pathogenesis and causes of HPE, and thus to improve the genetic counseling of patients and their families.